2013
DOI: 10.1103/physrevc.88.014910
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive photoproduction of radially excitedψ(2S)mesons in photon-Pomeron reactions in PbPb collisions at energies available at the CERN Large Hadron Collider

Abstract: In this work we investigate the photoproduction of radially excited vector mesons off nuclei in heavy ion relativistic collisions. In particular, we analyze the exclusive photoproduction of ψ(2S) off nuclei, evaluating the coherent and the incoherent contributions to that process. The theoretical framework used in the present analysis is the light-cone dipole formalism and predictions are done for PbPb collisions at the CERN-LHC energy of 2.76 TeV. The theoretical uncertainties are analyzed and comparison is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…[7], the gluon shadowing correction was introduced and the model sensitivity was analyzed. It was found that a strong model dependence on predictions existed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7], the gluon shadowing correction was introduced and the model sensitivity was analyzed. It was found that a strong model dependence on predictions existed.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we consider the energy dependence of the slope using a Regge motivated expression [6]. In our numerical calculation, corrections for the skewedness and real part of the amplitude have also been included [7]. On the other hand, the exclusive photoproduction off nuclei for coherent processes can be computed in a simple way in the large coherence length c R A limit [8,9]:…”
Section: Theoretical Framework and Main Expressionsmentioning
confidence: 99%
“…The cross section is compared to the same set of models as for the J/ψ. The GM model was updated to the GDGM model [15] using the by then published measurement of coherent J/ψ production. Again the EPS09 parameterisation describes best the data.…”
Section: Coherent Production Of ψ(2s)mentioning
confidence: 99%
“…The detailed analysis related to the radial excitations of charmonia was investigated in Refs. [9][10][11], where the momentum transfer distribution has been also addressed.…”
Section: Introductionmentioning
confidence: 99%